Effect of the SARS-CoV2 Pandemic on Endoscopy Provision – The Impact of Compliance with National Guidance. (3rd April 2021) - Leeds, John S; Awadelkarim, Bidour; Dipper, Christian; Nayar, Manu K; Oppong, Kofi W; Nylander, David L
ABSTRACT: Objective : There are limited data on the impact of the pandemic upon endoscopy service provision and quality indicators. Methods : Analysis of number and type of procedure, in-room time (minutes), key performance indicators, and list utilization was performed over three periods; pre-lockdown, lockdown, and early recovery and compared with the previous year. Results : Endoscopy activity reduced to 13.3% of the same period in 2019 with the largest drops in colonoscopy and flexible sigmoidoscopy numbers. In-room time increased significantly for gastroscopy (35 vs. 24, p < 0.0001), flexible sigmoidoscopy (20 vs. 15, p < 0.0001), endoscopic ultrasound (40 vs. 32, p = 0.0009), and ERCP (59 vs. 45, p = 0.0041). There was no increase for colonoscopy (35 vs 35, p = 0.129). There was a significant reduction in in-room time for gastroscopy alone (44.5 vs. 30.0, p = 0.0002) over the study period. There was no significant difference in cecal intubation rate, polyp detection rate, or biliary cannulation rate compared to the previous year. Conclusions : The pandemic has profoundly reduced the number of endoscopies performed with some recovery. In-room time has significantly increased but with the preservation of key performance indicators. List utilization remains a significant problem and resources need to be adequately aligned to improve this.